2008
DOI: 10.1136/thx.2007.089458
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome following lung transplantation in patients with cystic fibrosis colonised with Burkholderia cepacia complex: results from two French centres

Abstract: Background: Infection with Burkholderia cepacia complex (BCC) is a life threatening complication of cystic fibrosis (CF), often seen as a contraindication for lung transplantation. Methods: A long term retrospective study was conducted of all patients with CF undergoing lung transplants from January 1990 to October 2006 in two French centres allowing transplantation in patients colonised with BCC. Results: 22 of the 247 lung transplant patients with CF were infected with BCC (B cenocepacia genomovar III (n = 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 36 publications
3
63
0
3
Order By: Relevance
“…Two studies involving bacteremic or non-bacteremic SOT recipients with XDR Acinetobacter baumannii suggested that colistin-carbapenem combinations may result in improved clinical responses and survival, and may also limit the emergence of colistin resistance, with the durations of combination therapies ranging between 3 and 52 days [22,23]. In lung transplant recipients with MDR Pseudomonas aeruginosa infections, combination therapies included two or three different classes (beta-lactam + aminoglycoside ± fluoroquinolone) of antimicrobials for 10-14 days, and in non-lung SOT patients, shorter treatment durations (7-10 days) might be possible, depending on the infection site [56,58,59]. Combination therapies including piperacillin-tazobactam, carbapenems (except ertapenem), and/or trimethoprim-sulfamethoxazole should be favored for Achromobacter xylosoxidans infection [24,57].…”
Section: Therapy Of Mdr Gram-negative Bacteria Among Sot Recipients Wmentioning
confidence: 99%
“…Two studies involving bacteremic or non-bacteremic SOT recipients with XDR Acinetobacter baumannii suggested that colistin-carbapenem combinations may result in improved clinical responses and survival, and may also limit the emergence of colistin resistance, with the durations of combination therapies ranging between 3 and 52 days [22,23]. In lung transplant recipients with MDR Pseudomonas aeruginosa infections, combination therapies included two or three different classes (beta-lactam + aminoglycoside ± fluoroquinolone) of antimicrobials for 10-14 days, and in non-lung SOT patients, shorter treatment durations (7-10 days) might be possible, depending on the infection site [56,58,59]. Combination therapies including piperacillin-tazobactam, carbapenems (except ertapenem), and/or trimethoprim-sulfamethoxazole should be favored for Achromobacter xylosoxidans infection [24,57].…”
Section: Therapy Of Mdr Gram-negative Bacteria Among Sot Recipients Wmentioning
confidence: 99%
“…Infection with B. cepacia complex organisms can result in increased mortality and morbidity, including "cepacia syndrome," and it has been associated with person-to-person transmission and poor outcomes following lung transplantation (1)(2)(3)(4)(5). Currently, the B. cepacia complex comprises 17 distinct species (6,7).…”
mentioning
confidence: 99%
“…В мировой научной медицинской литературе до настоящего времени отсутствуют методические рекомендации или клинические обзоры по лече-нию данной группы пациентов после транспланта-ции легких, имеются лишь сообщения отдельных трансплантационных центров об удачных или не-удачных схемах послеоперационной антимикроб-ной терапии [13][14][15]. Успех лечения в нашем на-блюдении обусловлен, по-видимому, комбинацией агрессивной хирургической тактики, адекватной лекарственной терапии (применение больших доз противомикробных лекарственных средств с целью преодоления антибиотикорезистентности), редук-ции иммуносупрессии и применением гиперба-рической оксигенации (ГБО).…”
Section: Discussionunclassified